THE PHILOSOPHICAL ISSUES IN THE CONCEPT OF “PROFIL PELAJAR PANCASILA” - Shely Cathrin; Rukiyati Rukiyati; Arif Rohman; Reno Wikandaru (Sekolah Tinggi Agama Islam Sadra, 2024)
This research aims to identify and elaborate on the philosophical issues inherent in the concept of the Profil Pelajar Pancasila (Pancasila Student Profile) as the epitome of human idealism in Pancasila intended for implementation through educational means in Indonesia. This matter holds significance for examination due to the Pancasila Student Profile serving as the ultimate destination or objective of the complete educational system in Indonesia. Philosophical scrutiny of this concept is imperative to ensure alignment between the Pancasila Student Profile and the notion of the Indonesian ideal individual in line with Pancasila’s principles. This investigation adopts a qualitative method to delve into philosophical quandaries within this domain. The data utilized in this research comprises literary works addressing the Pancasila Student Profile, which are then philosophically scrutinized based on four key attributes: radical, critical, systematic, and comprehensive. The findings of this study reveal a philosophical dilemma within the Pancasila Student concept, specifically the underrepresentation of two vital dimensions of human nature in Pancasila, namely materiality and individuality. Consequently, it is recommended that a reassessment and restructuring of the Pancasila Student Profile concept be undertaken to ensure the realization of the ideal human archetype of Pancasila without straying from the educational objectives outlined in Law No. 20 of 2003 regarding the National Education System.